PELATIHAN PEMBERDAYAAN KELOMPOK WANITA PEMBUAT KERUPUK UBI UNGU DI DESA PADAHANTEN - Whydiantoro; Budiman Budiman; Engkos Koswara (BERNAS: Jurnal Pengabdian Kepada Masyarakat, 2021)
The purple sweet potato cracker product is the result of the creativity of the women's farmer group in Padahanten village. Until now, purple sweet potato crackers have not been able to become the main commodity in helping the economy of the women farmer group. Only a few members sell crackers. However, in practice sales are so small that they cannot be used as a reliable source of income. This is caused by various factors, one of the contributing factors is product packaging and product marketing. Product packaging currently only uses simple plastic without using a brand or logo, so it is less attractive to consumers. For marketing only through local residents and stalls in the village. In the manufacturing process, women farmer groups have not used tools/machines to speed up the production process. So it takes a relatively long time to produce crackers. In this community service activity, the packaging design will be made to the manufacture of marketing media in the form of web marketing. With this is expected to increase consumer interest and marketing. In addition, the manufacture of production equipment and training will be given to the women's farmer group in Padahanten Village in order to increase the production speed of the purple sweet potato cracker product.